ANALISIS PENGARUH PENAMBAHAN ABU CANGKANG KELAPA SAWIT TERHADAP STABILITAS DAN KEPADATAN ASPAL MODIFIKASI PG 76 (AC-WC) - Rosyad, Farlin; Prasetyo, Juwanda (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Roads are infrastructure that plays a very important role in the progress of a region, which is a link between one region and other regions. Asphalt concrete layer (Laston) is the most frequently used road pavement in Indonesia, consisting of asphalt, aggregate and filler. In an effort to add substitutes for fine materials that can be used as ingredients in asphalt mixtures, palm shell ash, which is easily obtained, was used in research as an alternative fine material in asphalt mixtures. The asphalt used in this research is PG 76 modified asphalt originating from PT. Perdana Eternal Mighty. This research was carried out with the aim of finding out the value of a mixture of palm shell ash as a fine fraction material for AC-WC layered laston in terms of stability and density. The percentage of palm shell ash content used in this research was 0%, 4%, 6% and 8%. This research uses the Marshall test method by reviewing the effect of palm shell ash on stability and density. Based on the results of testing the marshall parameters in terms of variations in the percentage of substitution content of palm shell ash, it can be concluded that the greater the content of palm shell ash used, the greater the value of stability and density, for the highest value obtained Stability was 1334 (residual marshall) at a variation of 6% and density of 2.297 in variation 8%Keywords: Palm shell ash, PG76 modified asphalt, AC-WC, Stability Density